The Caliphate as the Global Islamic Politics: Theological, Historical, and Contemporary Discourse Perspectives - Setiawan, Tomi (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2025)
This paper aims to explain the concept of caliphate in a theological and historical framework, while analyzing contemporary discourse. The caliphate is a system of leadership based on the Qur'an and Sunnah, with the example of the Rashidun Caliphates emphasizing justice, wisdom, and accountability. However, in an increasingly complex world, the relevance of the caliphate remains a matter of debate. Historically, the caliphate underwent a transformation from a representative model in early Islam to a monarchy. Moreover, the end of the Ottoman Empire marked the end of the classical caliphate and sparked discussions about its relevance today. This study concludes that the caliphate functions as a Sharia-based Islamic system of government to achieve social justice. Its value remains relevant as a model of ethical leadership that emphasizes justice, trust, and wisdom. However, its implementation requires contextual and inclusive reinterpretation to suit the needs of a modern, pluralistic society. Ultimately, the idea of the caliphate can be an inspiration without ignoring contemporary realities.